Encyclopedia of Inorganic and Bioinorganic Chemistry 2022
DOI: 10.1002/9781119951438.eibc2795
|View full text |Cite
|
Sign up to set email alerts
|

Phosphanylidenephosphoranes

Abstract: Phosphanylidenephosphoranes of the general formula RP(PR′ 3 ) have emerged as a powerful tool in synthetic inorganic chemistry and have found applications in the formation of phosphaalkenes using the so‐called phospha‐Wittig reaction, as well as valuable phosphinidene‐transfer reagents. In addition, the electron‐rich dicoordinate phosphanylidene P‐atom can be utilized in reactions with electrophiles and in the activation of EH bonds. Theoretical investigations clearly show that these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 115 publications
0
9
0
Order By: Relevance
“…All hydrogen atoms are omitted for clarity. Selected bond lengths [Å] and angles [°]: P1À C1 1.8982 (10), C1À P2 1.9021 (10), P2À Cl1 2.0685(4); P1À C1À P2 112.95 (5). [14] with thermal ellipsoids plotted at 50 % probability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All hydrogen atoms are omitted for clarity. Selected bond lengths [Å] and angles [°]: P1À C1 1.8982 (10), C1À P2 1.9021 (10), P2À Cl1 2.0685(4); P1À C1À P2 112.95 (5). [14] with thermal ellipsoids plotted at 50 % probability.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9] However, we found that the scope of phosphinidene transfer was quite limited by the high thermal and photolytic stability of the PB-phosphinidene adducts. [9,10] As a result, we sought to modify the FLP chelate bite angle to facilitate the release of main group fragments for productive materials synthesis. Our first efforts in this regard involved preparing FLP ligands with increased bite angles as compared to PB, but these proved to be much less reactive due to a strong intramolecular PÀ B bonding in their uncomplexed forms.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Base-stabilized acyclic boraphosphenes have been studied in detail, [3] and NHCstabilized phosphaborenes with small silyl-substituents (B, Figure 1) have been described, that can engage in metathesis reactions through Me 3 Si-halide elimination. [3d] Our group has used phosphanylidenephosphoranes of the type ArP(PMe 3 ) (Ar = sterically demanding aryl group), [4] so-called phospha-Wittig reagents, [5] as phosphinidene transfer reagents, by substitution of PMe 3 with stronger Lewis bases. [6] The reaction of Ar TerP(PMe 3 ) (Ar=Dip (C), Tip (D) 2,4,6-iPr 3 -C 6 H 2 ; Ar Ter = 2,6-Ar 2 -C 6 H 3 , Figure 1) with (Cp*Al) 4 (Cp* = C 5 (CH 3 ) 5 ) afforded the first examples of phosphaalumenes Ar TerP=AlCp*, as violet compounds with a highly polarized PÀ Al multiple bond.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The presence of N-atoms adjacent to the PvC double bond results in an accumulation of π-electron density at the terminal dicoordinate phosphorus atom, akin to isovalence electronic N-heterocyclic olefins (NHOs), 6,7 N-heterocyclic imines (NHIs) 8 and phosphanylidenephosphoranes. 9 Bertrand and co-workers developed a scale based on the 31 P NMR shift of a series of PhPvNHC derivatives to quantify the π-accepting properties of the NHC bonded to phosphorus. PhPvNHC can be conveniently accessed by the treatment of PhPCl 2 with the respective NHC and subsequent reduction with Mg metal.…”
Section: Introductionmentioning
confidence: 99%